4x-6=-32

Simple and best practice solution for 4x-6=-32 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-6=-32 equation:


Simplifying
4x + -6 = -32

Reorder the terms:
-6 + 4x = -32

Solving
-6 + 4x = -32

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 4x = -32 + 6

Combine like terms: -6 + 6 = 0
0 + 4x = -32 + 6
4x = -32 + 6

Combine like terms: -32 + 6 = -26
4x = -26

Divide each side by '4'.
x = -6.5

Simplifying
x = -6.5

See similar equations:

| 2x+14+3x-15=7 | | 5(t+2)=2(t+3) | | (2x-7)(x+3)(x-2)=0 | | (4x)+(3x-8)=90 | | x+x-20=54 | | 2x^2+2y^2+8x-12y+3=0 | | 8y+3=7y-7 | | 20-5/2 | | j^2+24j+23=0 | | 2(x-3)-4x=8-3(2x-1)+11 | | 2x+16=3x-25 | | 3x-25=2(y+8) | | 64=4+6(x+4) | | g^2-13g+22=0 | | j^2+6j=0 | | d^2-50d=0 | | 17y*3= | | (-9/7)x1/2/11x(-1/6) | | 5x+58=x+26 | | (a-2)*(a-2)= | | (6ln(7))-(6ln(1))= | | 9(d-4)-6=8(d-8)+46 | | 6x+30=2x+6 | | (h+7)(h-2)h=72 | | 4(2x-1)-2(x+3)=5 | | 5(r+5)=2(r-4)+1 | | 4U^3=64u | | x(670-x)=.35 | | (670-x)/x=.35 | | =x^2+mx-2x | | 5x+12=4x+2 | | -3(4y-6)+6y=4(y+4) |

Equations solver categories